Transforming the Role of Female Ulama: Countering Patriarchal Interpretations Through Digital Preaching and Islamic Education - Muhibatul Muyasyaroh; Nabilah Nurjannah; Rufaidah; Abdul Fadhil (Konsultan Jurnal Ilmiah Indonesia, 2025)
Gender inequality resulting from patriarchal religious interpretations has prompted female Islamic scholars to take a more active role in presenting a justice-oriented understanding of Islam. In the digital context, this role has evolved through the production of Islamic preaching and educational content that is more adaptive. This research aims to describe the transformation of female Islamic scholars' roles, strategies for utilizing digital media, and their contributions to strengthening gender equality values. This study employs a descriptive analytical qualitative method based on Systematic Literature Review (SLR) through library research and digital content analysis, analyzed using a gender hermeneutics framework and Berger & Luckmann's social construction theory. The research findings indicate that female Islamic scholars utilize digital spaces to challenge patriarchal interpretations through critical and inclusive religious narratives, build more egalitarian religious authority through open interactions with audiences, and strengthen the ummah's gender literacy by presenting Islamic materials that emphasize principles of justice and women's experiences in religious practice.